Learning outcomes measured in zoo and aquarium conservation education. Issue 1 (27th May 2022) - Schilbert, Jana; Scheersoi, Annette
Abstract: Communicating the topic of conservation to the public and encouraging proenvironmental behaviors can mitigate loss of biodiversity. Thus, the evaluation of educational efforts is important to ascertain the educational effects and provide high‐quality conservation education. The learning outcomes of conservation education are diverse (e.g., attitudes, knowledge, and behavior). Considering the specific characteristics of these different outcomes and the factors that influence them is crucial to delivering successful conservation education. We reviewed 29 peer‐reviewed articles published in English from January 2011 to April 2020 on empirical studies of learning outcomes of on‐site conservation education in zoos and aquaria, institutions that seek to educate the public about conservation. We examined the range of learning outcomes, their definitions, and factors that influenced them. Cognitive outcomes were most frequently investigated (37%) in comparison with other outcomes (e.g., affective outcomes, 31%). The articles did not use explicit definitions for learning outcomes, and implicit or explorative definitions provided were inconsistent. Outcomes were influenced by various factors (e.g., prior experiences, staff interaction, animal behavior). Our results suggest the agenda of conservation education research should be broadened by examining all learning outcomes relevant to behavior change. Educational and behavior change theories should be used as a background for conservation education research to ensure clear and consistent definitions, derive appropriate instruments to measure learning outcomes, and relate learning outcomes to influencing factors. We recommend conservation education researchers and practitioners to treat conservation education holistically and acknowledge its learning outcomes' full complexity. Abstract : Resultados del Aprendizaje Medidos en la Educación para la Conservación en Zoológicos y Acuarios Resumen: La comunicación del tema de conservación y el fomento de las conductas proambientales entre el público puede mitigar la pérdida de la biodiversidad. Así, la evaluación de los esfuerzos educativos es importante para determinar sus efectos y proporcionar una educación para la conservación de gran calidad. Los resultados del aprendizaje de la educación para la conservación son diversos (p.ej.: actitudes, conocimiento y comportamiento). Es importante considerar las características específicas de estos diferentes resultados y los factores que les influyen para proporcionar una educación para la conservación exitosa. Analizamos 29 artículos, revisados por pares y publicados en inglés entre enero de 2011 y abril de 2020, sobre los estudios empíricos de los resultados del aprendizaje de la educación para la conservación in situ en zoológicos y acuarios, instituciones que educan al público sobre la conservación. Analizamos la variedad de resultados del aprendizaje, sus definiciones y los factores que les influyen. Los resultados cognitivos fueron los que se investigaron con mayor frecuencia (37%) en comparación con otros resultados (p.ej.: resultados afectivos, 31%). Los artículos no usaron definiciones explícitas para los resultados del aprendizaje, y las definiciones implícitas o exploratorias que se proporcionaron fueron incoherentes. Los resultados estuvieron influenciados por diversos factores (p.ej.: experiencias previas, interacción con el personal, comportamiento animal). Nuestros resultados sugieren que la agenda de la investigación sobre la educación para la conservación debería extenderse mediante la examinación de los resultados del aprendizaje relevantes para el cambio en el comportamiento. Las teorías del cambio educativo y conductual deberían usarse como trasfondo para la investigación sobre la educación para la conservación para garantizar definiciones claras y concisas, derivar instrumentos adecuados para medir los resultados del aprendizaje y relacionar los resultados del aprendizaje con los factores influyentes. Recomendamos que los investigadores y los practicantes de la educación para la conservación la manejen de forma holística y reconozcan toda la complejidad de sus resultados de aprendizaje.